2021
DOI: 10.1002/ppul.25684
|View full text |Cite
|
Sign up to set email alerts
|

Early‐onset, fatal interstitial lung disease in STAT3 gain‐of‐function patients

Abstract: Gain-of-function variants in STAT3 are known to cause severe, multifaceted autoimmunity. Here we report three individuals with de-novo STAT3 GOF alleles and early-onset, severe interstitial lung disease manifesting during the first 3 years of life. Imaging and histology revealed different forms of interstitial pneumonia alongside fibrotic and cystic tissue destruction. Definitive diagnosis was established by postmortem whole exome sequencing and functional validation of two new STAT3 variants. Such lung-predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…So far, there is no standard treatment guideline available for STAT3 GOF syndrome ( 10 , 11 ). Nontargeted immunosuppressive therapies were found to be overall ineffective in STAT3 GOF-related ILD, potentially increasing the risk of infections ( 12 15 ). The monotherapy with tocilizumab is also insufficient to improve respiratory status ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, there is no standard treatment guideline available for STAT3 GOF syndrome ( 10 , 11 ). Nontargeted immunosuppressive therapies were found to be overall ineffective in STAT3 GOF-related ILD, potentially increasing the risk of infections ( 12 15 ). The monotherapy with tocilizumab is also insufficient to improve respiratory status ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both the immunosuppressive agents and targeted treatments have been reported. Whereas the former drugs were found to be overall ineffective, and instead, they increased the risk of infections ( 12 15 ). Targeted treatments such as JAK inhibitors and monoclonal antibodies against the interleukin 6 (IL-6) receptor have been proven to target the JAK-STAT pathway indirectly and shown promising results in STAT3 GOF diseases ( 4 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the STAT3 protein family is closely related to the inflammatory response and immune response. As a transcription factor, STAT3 can participate in the regulation of the expression of inflammation-related genes (24,25). At the same time, a study has shown that STAT3 is closely related to the degree of tissue fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause is pre-term delivery; in this clinical context the term chronic neonatal lung disease (CNLD) has been established for children requiring oxygen for >28 days after birth (figure 4) [51]. Comparable forms of alveolar simplification are the sequelae of pulmonary hypoplasia, either as a primary form associated with genetic abnormalities (NKX2-1 (NK2 homeobox 1; alias TTF1 (thyroid transcription factor 1)) deficiency, FLNA (filamin A) mutation, trisomy 21) (figure 5 and supplementary figure S1), or as a secondary form with impaired lung unfolding triggered by diaphragmatic hernia, oligohydramnios, thoracic skeletal dysplasia or neuromuscular disease (supplementary table S1 and figure 2) [7,44,45,52].…”
Section: Diffuse Growth Abnormalities Of Lung Parenchyma (A2)mentioning
confidence: 99%